The Role of Collective Management Organizations in Providing Legal Protection to Creators of Musical Works and Songs - Anita Sabara Sutphin; Dhaniswara K. Harjono; John Pieris; Hulman Panjaitan (Leges Privatae, 2026)
The rapid development of the music industry, driven by digital technology, has significantly transformed the creation, distribution, and consumption of musical works, while simultaneously increasing challenges related to copyright protection. In this context, collective management organizations (CMOs) play a strategic role as intermediaries in managing creators’ economic rights, particularly in licensing, royalty collection, and distribution. This study aims to examine the role of CMOs in providing legal protection for creators of musical works and songs, as well as to analyze the challenges affecting their effectiveness. This research employs a qualitative approach with a descriptive design, combining normative legal analysis with a limited empirical perspective. Data were collected through library research using primary, secondary, and tertiary legal materials, and analyzed using a descriptive-analytical method to identify patterns, relationships, and key issues related to the functioning of CMOs. The findings indicate that CMOs are essential in simplifying the management of economic rights and ensuring more structured and efficient royalty systems. However, their effectiveness is influenced by several factors, including low public awareness of copyright obligations, weak law enforcement, and gaps between regulatory frameworks and practical implementation. Additionally, internal challenges such as limited transparency, accountability issues, and varying levels of institutional capacity affect creators’ trust in these organizations. The study also highlights that digital technological advancements require CMOs to adapt through the adoption of data-driven systems to improve monitoring and royalty distribution. In conclusion, while CMOs hold a crucial position in strengthening legal protection for creators, their optimal performance depends on the synergy between effective governance, technological adaptation, strengthened law enforcement, and increased public awareness. Enhancing these aspects is essential to establish a fair, transparent, and sustainable copyright protection system that supports the growth of the music industry.